Paul of Dune [compact disc, unabridged] - Herbert, Brian (Herbert, Frank. Dune series., 2008)
Herbert and Anderson share the story of how Paul Muad'Dib gained control of the universe. Paul has become the religious figure of a powerful empire, but even he is beginning to doubt himself and those closest to him.